Supervisi Pendidikan Islam dalam Konsep Al-Qur’an dan Hadist - Fajri Dwiyama (Institusi Agama Islam Negeri (IAIN) Bone, 2023)
This article aims to obtain an overview of the supervision of Islamic education.Â Supervision of Islamic education is the process of providing directed, continuous and systematic assistance to each individual in order to develop their potential or religious nature optimally by internalizing the values contained in the Quran and hadith. The research method used is review literature, by looking for various articles, books, that discuss this. The Qur'an and Hadith are the main foundations for writing this article. This research was conducted by reading, studying, and analyzing various existing literature. The results of the study concluded that the concept of spiritual transcendental supervision of educators in the Qur'an and hadith cannot be separated from the concept of a Muslim's belief in Allah Almighty. and its Apostles